Implementation Of Integrated Governance: A Case Study At Pt Xyz Group - Fidinilah, Efi; Sudrajad, Oktofa Yudha (UNIVED Press, 2026)
PT XYZ, as a state-owned enterprise in the energy sector, faces challenges in implementing appropriate integrated governance. The latest regulation, Permen SOEs No. 02/MBU/03/2023, emphasizes the importance of implementing integrated governance encompassing risk management, internal audit, and compliance. Therefore, an adaptive, effective, and efficient integrated governance model is needed, capable of addressing the weaknesses of the current silo approach while consistently strengthening GCG across all group entities. The purpose of this study is to analyze the structure of risk management organs in each subsidiary, identify and formulate relevant parameters for designing an effective and optimal integrated governance model or policy, and develop a roadmap for implementing integrated governance in the PT XYZ Group. Data were collected through primary and secondary data. Primary data were obtained through questionnaires, while secondary data were obtained from PT XYZ's annual reports. The analysis was conducted using the Analytical Hierarchy Process (AHP) method based on three main parameters: (1) Business Line (directly connected to the parent supply chain, not related to the supply chain but supporting the RJPP pillars, not supporting both), (2) Size and Contribution (assets, capital, net profit), and (3) Status and Share Ownership (operational, controlling, non-controlling). The findings show that based on the analysis of the hierarchy process (AHP), the priority weights of the criteria in the entity assessment are Business Line (59.6%), Status & share ownership (22.8%), and size & contribution (17.5%). The AHP results confirm that subsidiaries in the core supply chain and with operational status have the highest priority in strengthening governance. Based on the risk classification, this study simplifies the entity types into three categories: Type 1, Type 2 and Type 3 and this study compiles a three-stage roadmap (short, medium, and long term). This study recommends that strengthening integrated governance in PT XYZ Group must be carried out gradually and proportionally.